Pain characterization in knee osteoarthritis - Soni, A (2015)
Osteoarthritis (OA) is the most common form of arthritis in the world, and it has been estimated that about one tenth of the world’s population, aged over 60, have symptoms that can be attributed to OA. Despite the size of the global impact of OA, there is a significant unmet need for effective treatments. Knee replacement surgery is commonly used in patients with moderate to severe knee OA, in order to reduce pain. However, 10-34% of patients report an unfavourable long-term outcome with persistent pain after surgery. The neural mechanisms for the generation of pain in knee OA are not fully understood. Previous work has shown that around 20% of patients have features of neuropathic pain, and that the underlying mechanism for this may be through central sensitisation. This mechanism-based understanding of pain is important in order to aid targeted intervention, and it may be that this patient group is more likely to have an adverse outcome following surgery. This thesis uses a combination of methods to investigate the neural mechanisms underlying pain experienced by patients with knee OA, across the full spectrum of disease severity. Quantitative sensory testing (QST) was initially used in a community-based cohort to show that pain sensitisation can be detected in early disease, and also contributes to the observed discordance between radiographic structural and symptomatic disease. The clinical relevance of neuropathic pain was then investigated in patients with knee OA, who were awaiting knee replacement surgery. Prior to surgery patients with neuropathic pain had increased sensitivity to experimental pain, as well as higher symptom severity and psychological distress. Functional magnetic resonance imaging (fMRI) was then used to confirm that these features were also associated with central sensitisation in the form of increased descending facilitation as well as reduced descending inhibition prior to surgery. The presence of neuropathic pain prior to surgery was associated with statistically and clinically significantly worse outcome following surgery, compared to those with purely nociceptive pain in the absence of any significant structural differences between the two groups. Taken together, this mechanism-based understanding of the pain provides an opportunity for targeted therapy prior to surgery, which may enhance outcome following surgery.